Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/coatings11050552
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Properties of Laser Cladding Fe-Based Alloy Coating on 27SiMn Steel Surface

Abstract: In this paper, the corrosion performance of a laser cladding Fe-based alloy coating on the surface of 27SiMn steel was studied. The Fe-based alloy coating was prepared on a 27SiMn steel surface by high-speed laser cladding. The microstructure, morphological characteristics, element content, and phase composition of the cladding layer were analyzed by an optical microscope (OM), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), and X-ray diffractometer (XRD), respectively. The corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Currently, although there have been relatively numerous studies focused on optimizing cladding structure and processes to enhance substrate performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders remains relatively limited [8]. Common metallurgical bonding technologies between barrel substrates and claddings include overlay welding [9,10], thermal spraying [11,12], electric spark deposition [13,14], and laser cladding [15][16][17]. The study revealed that by conducting PTA welding on the surface of E32 steel, a surfacemodified cladding consisting of tungsten carbide reinforced cobalt was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, although there have been relatively numerous studies focused on optimizing cladding structure and processes to enhance substrate performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders remains relatively limited [8]. Common metallurgical bonding technologies between barrel substrates and claddings include overlay welding [9,10], thermal spraying [11,12], electric spark deposition [13,14], and laser cladding [15][16][17]. The study revealed that by conducting PTA welding on the surface of E32 steel, a surfacemodified cladding consisting of tungsten carbide reinforced cobalt was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…27SiMn steel is a kind of low-alloy structural steel that is mainly used to manufacture hot stamping parts and is widely used in coal machinery, thermal power generation, geological drilling, and other fields [1]. Regarding the development of 27SiMn steel, a large number of previous studies have mainly concentrated on the 'steel after'.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [9] performed laser melting carbon powder on the surface of U71Mn steel with purpose of improving the resistance to rolling fatigue wear. Fe-based self-fluxing coating was prepared on U71Mn steel, the average microhardness of the coating can reach 780 HV, which is significantly higher than that of the fusion zone and the substrate, meanwhile, no cracks in the coating were found even applied 453 kN static load on it [10]. The microhardness of the U71Mn steel was improved by 3.7 times by preparing Ni60-25%WC coating on it [11].…”
Section: Introductionmentioning
confidence: 99%